PERBEDAAN EFEKTIVITAS MENYIKAT GIGI METODE HORIZONTAL DAN METODE FONES TERHADAP PENURUNAN INDEKS PLAK GIGI PADA ANAK TUNANETRA USIA 6-13 TAHUN DI SEMARANG - Muthia Choirunnisa; Prima Agusmawanti; Moh Yusuf (Odonto : Dental Journal, 2015)
Introduction: Children with special needs have physical limitations and the ability to maintain their oral hygiene, so it needs to be chosen the proper tooth brushing methods for maintaining oral hygiene and prevent periodontal disease.Purpose: This study aimed to know differences of the effectiveness of horizontal tooth brushing methods and foneson the dental plaque index in children with visual impairment.Methods: This research was a quasy experimental laboratory with pre-test and post-test design. The study was conducted on 26 blind children aged 6-13 years in MILB YKTM Budi Asih, SLB-A DriaAdi, and SLB Negeri Semarang that were divided into two groups of horizontal and fonestooth brushing method. Dental plaque was measured using PHP plaque index, examined the dental crown facial or lingual parts by dividing each tooth crown into 5 subdivisions, plaque index inspected before and after 1 week of brushing method application, then analyzed by paired t-test and independent t test at a significance level ofp <0.05. Results: The mean of plaque index before and after brushing the teeth with horizontal method was 2.56 and 0.956 down to 1.61, whereas in the fonesmethod was 3.03 and 1.68down to 1.35. Plaque index before and after brushing teeth both on horizontal and fones method was statistically significant(p <0.05). But the effectiveness of both methods were not different or similar (p = 0.179).Conclusion: There was no difference of effectiveness between horizontal and fones tooth brushing methods on the dental plaque index in children with visual impairment.